Media Kartu Huruf dalam Pengenalan Huruf Abjad Siswa Kelas 01 SD Muhammadiyah 01, Bengkulu. - Candika; Elintia Hanifah; Eli Rustinar (CV. Multi Kreasi Media, 2022)
Letter cards are alphabets written on pieces of a medium, be it cardboard, paper or blackboard (plywood) as learning media that use rectangular thick paper on which certain letters or letter elements are written or marked. Letter card media is expected to help students in the learning process. It is hoped that students will achieve positive learning outcomes during the learning process. The dedication activity using letter card media aims to improve students' ability to recognize letters of the alphabet at the elementary school level through the Introduction to Schooling Field (PLP) 2 at SD Muhammadiyah 01, Bengkulu City. This service is carried out by observation, preparation for making letter card media, implementation, and evaluation of learning outcomes. It is hoped that with this media students will more easily understand and recognize the letters of the alphabet. The results of the service show that students' ability to recognize letters of the alphabet is increasing in grade 1 students at SD Muhammadiyah 01, Bengkulu City.